Haustorium Inducing Factors for Parasitic Orobanchaceae - Goyet, Vincent; Wada, Syogo; Cui, Songkui; Wakatake, Takanori; Shirasu, Ken; Montiel, Gregory; Simier, Philippe; Yoshida, Satoko (Frontiers in Plant Science, 2019)
Parasitic plants in the Orobanchaceae family include devastating weed species, such as Striga, Orobanche and Phelipanche, which infest important crops and cause economic losses of over a billion US dollars worldwide, yet the molecular and cellular processes responsible for such parasitic relationships remain largely unknown. Parasitic species of the Orobanchaceae family form specialized invasion organs called haustoria on their roots to enable the invasion of host root tissues. The process of forming haustoria can be divided into two steps, prehaustorium formation and haustorium maturation, the processes occurring before and after host attachment, respectively. Prehaustorium formation is provoked by host-derived signal molecules, collectively called haustorium-inducing factors (HIFs). Cell wall-related quinones and phenolics have been known for a long time to induce haustoria in many Orobanchaceae species. Although such phenolics are widely produced in plants, structural specificities exist among these molecules that modulate their competency to induce haustoria in different parasitic plant species. In addition, the plant hormone cytokinins, structurally distinct from phenolic compounds, also trigger prehaustorium formation in Orobanchaceae. Recent findings demonstrate their involvement as rhizopsheric HIFs for Orobanche and Phelipanche species and thus address new activities for cytokinins in haustorium formation in Orobanchaceae, as well as in rhizospheric signaling. This review highlights haustorium-inducing signals in the Orobanchaceae family in the context of their host origin, action mechanisms, and species specificity.